A comprehensive prognostic and immunological analysis of ephrin family genes in hepatocellular carcinoma - Huang, Shenglan; Dong, Cairong; Zhang, Jian; Fu, Shumin; Lv, Yaqin; Wu, Jianbing (Frontiers in Molecular Biosciences, 2022)
Background: Ephrins, a series of Eph-associated receptor tyrosine kinase ligands, play an important role in the tumorigenesis and progression of various cancers. However, their contributions to hepatocellular carcinoma (HCC) remain unclear. Thus, we aimed to explore their prognostic value and immune implications in HCC. Methods: Multiple public databases, such as TCGA, GTEx, and UCSC XENA, were used to analyze the expression of ephrin genes across cancers. Kaplan–Meier analysis and Cox regression were used to explore the prognostic role of ephrin genes in HCC. A logistic regression model was utilized to evaluate the association between ephrin gene expression and clinical characteristics. Gene set enrichment analysis (GSEA) was conducted to elucidate their potential biological mechanisms. Various immune algorithms were utilized to investigate the correlation between ephrin genes and tumor immunity. We also analyzed their association with drug sensitivity, and gene mutations. Finally, RT–qPCR was performed to validate the expression of ephrin family genes in HCC cells and clinical tissues. Results: The expression of EFNA1, EFNA2, EFNA3, EFNA4, EFNB1, and EFNB2 was upregulated in most cancer types, while EFNA5 and EFNB3 was downregulated in most cancers. In HCC, the expression levels of EFNA1, EFNA3, EFNA4, EFNB1, and EFNB2 were significantly higher in tumor tissues than in normal tissues. High expression of EFNA3, EFNA4, and EFNB1 was associated with tumor progression and worse prognosis in HCC patients. The expression of EFNA3 and EFNA4 was negatively associated with the stromal/ESTIMATE scores, while EFNB1 was positively correlated with the immune/stromal/ESTIMATE scores. Moreover, these ephrin genes were closely relevant to the infiltration of immune cells, such as B cells, CD4+ T cells, CD8+ T cells, neutrophil cells, macrophage cells, and dendritic cells. EFNB1 expression was positively associated with most immune-related genes, while EFNA3/EFNA4 was positively related to TMB and MSI. In addition, EFNA3, EFNA4, and EFNB1 were related to drug sensitivity and affected the mutation frequency of some genes in HCC. Conclusions: EFNA3, EFNA4, and EFNB1 are independent prognostic factors for HCC patients and are closely correlated with tumor immunity, which may provide a new direction for exploring novel therapeutic targets and biomarkers for immunotherapy.